Creative accounting. - Chuang, Teck Hai. (2013)
The objective of this applied research project is to look for suggestive evidence as to whether creative accounting is being practised in Singapore. The scope of this project is mainly based on the public companies that are currently listed on the stock exchange of Singapore. The methodology involves reviews of literature, distribution of surveys, analysis of financial statements, speculation and conclusion of our findings. Based on the research findings, there are some indicative evidence, albeit limited, that creative accounting may be practised in Singapore via the four common methods of creative accounting by some construction & property development and manufacturing companies. The four methods are the Capitalisation of Costs, the Classification of Extraordinary and Abnormal Items, Provision For Bad Debts and the Timing of the Disposal of Fixed Assets.